Optimizing Production of Fashion Goods as Means to a More Sustainable Garment Industry – An Assessment of the Literature - Katharina A. Schuck; Jens K. Perret (Research Journal for Applied Management (RJAM), 2023)
Objectives: The overall objective is to create awareness that production scheduling methods represent highly val-uable tools in contributing to a more sustainable garment manufacturing. Further, a structured illus-tration of existing objectives of production scheduling is provided by grouping them according to their influence on the production runs. Based on this, it is demonstrated how each of the six groups would entail beneficial sustainability effects. Theoretical Framework: The theoretical framework is based on six decades of research, which produced a broad range of con-tributions to production scheduling for different production layouts and designs (flow-shop, job-shop, assembly lines), covering the full range of fashion production designs. Method: Methodologically, a literature review and an accompanied analysis are provided. Results/Implications: While the economic advantages of production planning are obvious, the discussion revealed that liter-ature already contains considerable potentials for optimizing garment production, which, however, need to be applied to the fashion context, especially when it comes to enhanced sustainable business practices. As the link between optimization and holistic sustainability has received limited attention, this article presents a comprehensive conceptual view on the topic and provides decision makers and researchers with valuable inputs on which optimization approaches can support a company's sustain-ability efforts.
Keywords: 650; Sustainability; fashion; optimization; job-shop; flow-shop; assembly line